Fiscal institutions and fiscal management in Korea : evaluation and improvement of recent changes (Korea Institute of Public Finance SeoulKR, 2012)
Aims to assess current fiscal controls and fiscal operating systems in Korea and proposes detailed policy alternatives for adoption by the incoming administration.
Keywords: FISCAL POLICY